Sensory Over‐Responsiveness among Healthy Subjects is Associated with a Pronociceptive State. - Weissman‐Fogel, Irit; Granovsky, Yelena; Bar‐Shalita, Tami (Pain Practice, 2018)
Abstract: Objective: Chronic pain patients show hypersensitivity to sensory nonpainful stimuli. Sensory over‐responsiveness (SOR) to innocuous daily stimuli, experienced as painful, is prevalent in 10% of the healthy population. This altered sensory processing may be an expression of overfacilitation, or a less efficient pain‐inhibitory process in the pain pathways. We therefore aimed to investigate specifically the pain‐inhibitory system of subjects with SOR who are otherwise healthy, not studied as of yet. Methods: Thirty healthy subjects, divided into an SOR group (n = 14) and a non‐SOR group (n = 16) based on responses to the Sensory Responsiveness Questionnaire, were psychophysically tested in order to evaluate (1) hyperalgesic responses; (2) adaptation/sensitization to 14 phasic heat stimuli; (3) habituation; (4) 6‐minute after‐sensations; and (5) conditioned pain modulation (CPM) (ie, phasic heat stimuli applied with and without hand immersion in a hot water bath). Results: The SOR group differed from the non‐SOR group in (1) a steeper escalation in NPS ratings to temperature increase (P = 0.003), indicating hyperalgesia; (2) increased sensitization (P < 0.001); (3) habituation responses (P < 0.001); (4) enhanced pain ratings during the after‐sensation (P = 0.006); and (5) no group difference was found in CPM. Conclusions: SOR is associated with a pronociceptive state, expressed by amplification of experimental pain, yet with sufficient inhibitory processes. Our results support previous findings of enhanced facilitation of pain‐transmitting pathways but also reveal preserved inhibitory mechanisms, although they were slower to react.